STUDI KOMPARASI ANTARA LEMBAGA MADRASAH DAN NON MADRASAH TINGKAT MENENGAH ATAS DI KUDUS (STUDI KASUS DI MA NU MIFTAHUL FALAH DAN SMK NU MIFTAHUL FALAH) - Siti Nurrahayu Putri (Atta'dib Jurnal Pendidikan Agama Islam, 2020)
AbstractThis writing presents a comparison between the institutions a madrasah with non-madrasah agencies avaible in the Kudus area. Neither the madrasah or non-madrasah institutions are actually as good. But it has its distinct preeminence between such agencies that makes its own appeal. The purpose of this writing was to find out why the madrasah educational institutions was more of a Kudus society than non-madrasah educational society.besides, become the favorite and whether the curriculum in madrasah education institutions and non-madrasah education are the same or different. So we as writers are particulary interested in examing the comparative study between the madrasah and non-madrasah eduactional society. In this study writers have used field research because the main dta source used by the writers to take down the problem has to be collected in data fields, and to support in this article, writer also uses other sources of literature, where writers use sunch books, journals and research associated with this study.Keywords: madrasah, curriculum, society of Kudus.